Management of Deciding Decision Making Final Project Advisor in Optimizing Learning - Kamil, Mustofa; Rianto, Joko; Suprayogi, Danang (APTISI Transactions on Management (ATM), 2018)
In the management of learning in preparing the final assignment has become an obligation in each university. So, the existence of a final assignment supervisor is very important to help students complete their final assignments. Without the final assignment supervisor can lead to unclear and a directed research in accordance with the provisions of learning management, in this study discusses the role of lecturers in conducting final assignments in both thesis and thesis, lecturers as facilitators start the final assignment, lecturers as final project supervisors, lecturers as a final assignment exam preparation supervisor, stress in preparing the final assignment, communication of students with supervisors, choosing supervisors, consulting techniques with counselors, obstacles during the guidance of the preparation of the final assignment report. With the hope of this research students can choose a mentor where they must master the fields that are in accordance with your final assignment and with the provisions of learning management in Higher Education, and choose a mentor who has enough time to guide you, and a cooperative and communicative guide.